Sustainability and Education. Innovation Technology, Green Jobs, Generative Enterprises - Alessandra Vischi (University of Bologna, 2018)
Responsibility towards future generations requires a global ecological transformation. The environmental issue urges the sciences, first of all pedagogy, to reflect on the relationship between educability and technology, the pursuit of well-being and the authenticity of lifestyles. In recent years, sustainability and circular economy are concepts that have gained considerable popularity and attracted growing attention from the public. The article presents a pedagogical interpretation regarding the correlation between education, innovation and green works, with particular reference to sustainability, in the light of the ambiguity and the multiple meanings assumed in the current cultural debate.